Call for Papers: Intergenerational Justice Prize 2020 - FRFG, IF (Foundation for the Rights of Future Generations, Intergenerational Foundation) (Intergenerational Justice Review)
The Stuttgart-based Foundation for the Rights of Future Generations (FRFG) and the London-based Intergenerational Foundation (IF) jointly award the biennial Intergenerational Justice Prize, endowed with EUR 10,000 (ten thousand euros) in total prize-money, to essay-writers who address political and demographic issues pertaining to the field of intergenerational justice. The prize was initiated and is funded by the Apfelbaum Foundation. For the 2020 prize, the FRFG and IF call for papers on the following topic: Intergenerational wealth transfers through inheritance and gifts